Baduy Dalam Sentuhan Pariwisata: Studi Antropologi Tentang Perkembangan Pariwisata di Desa Kanekes dan Implikasinya - Noval Fariz Mutaqien; Ida Bagus Gde Pujaastawa; I Wayan Suwena (Sunari Penjor : Jurnal of Anthropology, 2021)
Kanekes Village is a tourism destination in Lebak Regency. The Baduy tribe is a native of Kanekes Village, they have customary rules that refuse the entry of modern culture into their culture. The unique culture of the Baduy people and their natural beauty are potential tourist attractions. Since it was established as a tourism destination, tourism in Kanekes Village has experienced developments ranging from tourist attractions, facilities, and various aspects of their lives. This study aims to describe the extent of tourism development in Kanekes Village and the implications, especially on socio-cultural, economic, and ecological aspects. The approach used in this study is a qualitative approach using the methods of observation, interviews, and literature study in data collection. The theory used in this research is the tourism area life cycle and the tourism impact theory. Based on the results of research in Kanekes Village, it was found that there was tourism development in several sectors such as tourist attractions and tourism facilities. The development of tourism in Kanekes Village provides both positive and negative impacts for the Baduy community. The implications of tourism development can be found in socio-cultural, economic, and ecological aspects.